Respirar, andar y luchar. La enmarcación de la tuberculosis en el encuentro paciente-funcionarias. Cali (2015-2017) - Figueroa Gómez, Jorge Enrique (Universidad Santiago de Cali, 2020)
Tuberculosis is still a serious public health concern worldwide. Cali has one of the highest rates of this disease in Colombia. For patients, Directly Observed Treatment Short Course (DOTS) is often even more difficult to bear than this disease. This therapy involves regular encounters with public health officials that provide the medication necessary for treatment. This research aims to show how this city ́s TB Programs' workers frame this disease, allowing patients greater adherence to treatment. The concept of "framework" is adopted from the work of Erving Goffman and Charles Rosenberg as well as the theoretical and methodological contributions from the Social Studies of Health and Science and Technology Studies. This research followed a qualitative perspective that included participant observation, field notes and in-depth interviews.